Hubungan antara Kepedulian Orang Tua dengan Keberhasilan Pendidikan Anak di Jorong Labuai Kabupaten Pasaman Barat - Fahriati Fahriati; Syuraini Syuraini (SPEKTRUM: Jurnal Pendidikan Luar Sekolah (PLS), 2018)
This research is motivated by the low education of children in Jorong Labuai Kecamatan Koto Balingka Kabupaten Pasaman Barat, this is thought to be one of the causes due to lack of concern for parents. This research aims to: (1) to describe the concerns of parents to children, (2) to describe the success of children's education, and (3) to see whether there is a relationship between parents' concern with the success of children's education. This research includes correlational quantitative research. The population in the research were children who dropped out of school and children who did not continue their education to the level SLTP, SLTA with the age of 13-18 years with a population of 57 people. Sampling technique stratified random sampling. The number of samples in this study is 30 people. Data collection techniques used questionnaires. Technique of data analysis by using formula of percentage and product moment. From the result of the research, it can be seen that: (1) the concern of the parents to the children low categorize, (2) the success of children's education in low category, and (3) there is a significant correlation between parental concern to the success of children's education in Jorong Labuai Kecamatan Koto Balingka, Kabupaten Pasaman Barat.Keywords: Concerns of Parents, Success of Children's Education